Effect of Seniority, Work Experience, and Competence on Promotion of Airport Maintenance Division Employees PT. Angkasapura II (Persero)Bandara Internasional Kuala Namu - Fajar Pradipto Utomo; R. Sabrina; Satria Tirtayasa; Hazmanan Khair (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the effect of seniority, work experience, and competence on job promotion in the Airport Maintenance Division of PT. Angkasapura II (persero) International Kualanamu Airport. This research uses a quantitative associative approach. The population in this study was in the Airport Maintenance Division of PT. Angkasapura II (persero) International Kualanamu Airport. The sample in this study used a saturated sample of 57 people. Data collection techniques through questionnaires that have been tested for validity and reliability. The data analysis used was the Structural Equation Model (SEM) method with the Partial Least Square (PLS) method. The results of this study indicate that: (1) Seniority has a significant positive effect on job promotion with a value of 0.356 and P-Values of 0.000. (2). Work experience has a significant positive effect on job promotion satisfaction with a value of 0.401 and P-values of 0.004. (3). Competence has a significant positive effect on job promotion with a value of 0.295 and P-values of 0.012. (4). Seniority, work experience, and competence simultaneously have a significant positive effect on job promotion